Preparation and characterization of paclitaxel palmitate albumin nanoparticles with high loading efficacy: an in vitro and in vivo anti-tumor study in mouse models - Hang Chen; Sifan Huang; Heyi Wang; Xinmei Chen; Haiyan Zhang; Youfa Xu; Wei Fan; Yun Pan; Qiuyan Wen; Zhizhe Lin; Xuena Wang; Yongwei Gu; et al. (Taylor & Francis Group, 2021)
Background Combination of the prodrug technique with an albumin nano drug-loaded system is a novel promising approach for cancer treatment. However, the long-lasting and far-reaching challenge for the treatment of cancers lies in how to construct the albumin nanometer drug delivery system with lead compounds and their derivatives. Methods In this study, we reported the preparation of injectable albumin nanoparticles (NPs) with a high and quantitative drug loading system based on the NabTM technology of paclitaxel palmitate (PTX-PA). Results Our experimental study on drug tissue distribution in vivo demonstrated that the paclitaxel palmitate albumin nanoparticles (Nab-PTX-PA) remained in the tumor for a longer time post-injection. Compared with saline and paclitaxel albumin nanoparticles (Abraxane®), intravenous injection of Nab-PTX-PA not only reduced the toxicity of the drug in normal organs, and increased the body weight of the animals but maintained sustained release of paclitaxel (PTX) in the tumor, thereby displaying an excellent antitumor activity. Blood routine analysis showed that Nab-PTX-PA had fewer adverse effects or less toxicity to the normal organs, and it inhibited tumor cell proliferation more effectively as compared with commercial paclitaxel albumin nanoparticles. Conclusions This carrier strategy for small molecule drugs is based on naturally evolved interactions between long-chain fatty acids (LCFAs) and Human Serum Albumin (HSA), demonstrated here for PTX. Nab-PTX-PA shows higher antitumor efficacy in vivo in breast cancer models. On the whole, this novel injectable Nab-PTX-PA has great potential as an effective drug delivery system in the treatment of breast cancer.